PERBANDINGAN STRATEGI PEMBELAJARAN TRADISIONAL DAN MODERN DI SMP BP TAHFIDZ AT TAUBAH KOTA BATAM - Anis Nirmala Patmawati; Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
A transformation of learning strategies in Islamic education from traditional methods centered on memorization and lectures to modern approaches that are interactive and technology-based is demanded by contemporary developments. This research is aimed at analyzing the comparative effectiveness of traditional and modern learning strategies in Islamic education and evaluating their compatibility with the principles of ijtihad as a foundation for innovation in contemporary Islamic educational contexts. A qualitative method with a descriptive-analytical literature review approach is employed in this study to examine classical and contemporary literature related to Islamic learning strategies and the concept of ijtihad. It is indicated by the findings that modern learning strategies demonstrate advantages in enhancing student engagement and developing critical thinking skills, while traditional strategies remain relevant in providing a strong knowledge foundation, and both approaches are aligned with the principles of ijtihad that promoted flexibility and adaptation in Islamic education. The integration of traditional and modern learning strategies in Islamic education is represented as a manifestation of contemporary ijtihad concepts that enable innovation in educational methods without abandoning the fundamental values of Islamic teachings.